Rozwój fizyczny i motoryczny 14 – letnich chłopców trenujących piłkę nożną = Physical development and motor 14 - year old boys trainees football - Klimczyk, Mariusz; Rydlewski, Gniewomir Rafał (Journal of Education, Health and Sport, 2016)
Klimczyk Mariusz, Rydlewski Gniewomir Rafał. Rozwój fizyczny i motoryczny 14 – letnich chłopców trenujących piłkę nożną = Physical development and motor 14 - year old boys trainees football. Journal of Education, Health and Sport. 2016;6(7):266-276. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57626 http://ojs.ukw.edu.pl/index.php/johs/article/view/3693 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. Rozwój fizyczny i motoryczny 14 – letnich chłopców trenujących piłkę nożną Physical development and motor 14 - year old boys trainees football Mariusz Klimczyk, Gniewomir Rafał Rydlewski Uniwersytet Kazimierza Wielkiego w Bydgoszczy E-mail: Klimczyk1956@poczta.onet.p Streszczenie Celem badań jest porównanie rozwoju fizycznego i motorycznego 14 letnich chłopców trenujących piłkę nożną z nietrenującymi rówieśnikami. W badaniach uczestniczyli chłopcy klas II gimnazjum. Próby zostały przeprowadzone w klasach uczonych przez jednego nauczyciela. W badaniach wzięło udział 33 uczniów uczęszczających do Gimnazjum nr 1 im. Henryka Sienkiewicza w Barcinie. Wszyscy badani byli w momencie badania w jednym wieku kalendarzowym (14 lat) i uznani przez pielęgniarkę szkolną za zdrowych. Zastosowano następujące metody badań: metody pomiarowej Martina. Badania obejmowały pomiar wysokości i masy ciała, wskaźnik BMI, badania sprawności fizycznej. Przy pomocy Międzynarodowego Testu Sprawności Fizycznej. Posłużono się następującymi statystycznymi: t-Studenta różnicy statystycznej dla grup zależnych, średnią arytmetyczną Rozwój fizyczny uczniów nie różni się według badań istotnie ani w miesiącu maju ani w październiku. Grupa badanych nietrenujących w okresie wakacyjnym osiąga wzrosty BMI istotne statystycznie. Uczniowie trenujący w okresie wakacyjnym osiągają mniejsze wzrosty wyników sprawdzianów motorycznych aniżeli nietrenujący rówieśnicy. Zarówno w przypadku siły ramion i skoku w dal wyniki członków obu grup w miesiącu maju i październiku były istotnie różne statystycznie, choć badani nietrenujący osiągnęli wyniki o istotności różnic na poziomie 1%. Największej zmianie uległy zdolności siłowe chłopców. Słowa kluczowe: rozwój fizyczny ,motoryczny, piłka nożna, trening, badania. Summary The aim of the study is to compare the physical and motor development 14 year old boys trainees football with no trainees peers. The study was attended by the boys Class II school. Trials were conducted in classrooms scholars by one teacher. The study involved 33 students attending School No. 1 for them. Henryk Sienkiewicz in Barcin. All subjects were in the time of the study in one calendar age (14 years) and recognized by the school nurse healthy. The following test methods: measuring method Martin. The research included measurement of height and weight, BMI, physical fitness tests. With the help of the International Physical Fitness Test. Was used with the following statistics: t-Student statistical difference for dependent groups, the arithmetic mean of physical development of students did not differ significantly according to the study or in the month of May or in October. Group surveyed untrained in the holiday season reaches a BMI increases statistically significant. Students who train during the holiday season to a smaller increase than the results of tests of motor no trainees peers. For both the arm strength and the long jump results of the members of both groups in the month of May and October they were significantly different statistically, although the subjects no trainees achieved results of the significance of differences at the level of 1%. The largest have changed the ability of the force boys. Keywords: physical development, motor, football, training, research.